Literature Review: Komposisi Isi Lambung Ikan Bandeng (Chanos chanos) di Indonesia (Isolation and Analysis of Proteolytic Activity of Local Actinomycetes from Aceh, Indonesia) - Nadya Tirta; Uswah Zilhaya; Firdus Firdus; Muhammad Nasir; Zainal Abidin Muchlisin (Jurnal Bioleuser, 2024)
Milkfish (Chanos chanos) is included as a fish with high economic value. Milkfish is often cultivated and developed by the community because of its relatively fast growth. The composition of milkfish food certainly affects the growth and development of fish so that fish farming can be carried out properly. Therefore, a literature review related to the composition of the stomach of milkfish is important. The study was conducted by searching, reviewing, and collecting appropriate library data regarding the composition of the stomach contents of milkfish (Chanos chanos) in Indonesia. Research related to the composition of the stomach contents of milkfish totaled 19 articles. The highest frequency of article publications in 2019 (5 articles). The composition of the stomach contents of milkfish consists of zooplankton, phytoplankton, detritus, and plant fragments. The type of food most consumed by milkfish is phytoplankton from the Chlorophyta and Cyanophyta groups.